Medication errors in children - Alsulami, Zayed Nama F. (2013)
Medication errors are a significant global concern and can cause serious medical consequences in children. Double checking of medicines by two nurses is one strategy used by many children's hospitals to prevent errors from reaching paediatric patients. This thesis involves different studies that evaluated the effectiveness of the double checking process in reducing and preventing medication administration errors in a children's hospital. In addition, a systematic review was conducted of medication errors studies in the Middle East. A systematic review was also conducted of published studies of double checking. Six electronic databases were searched for articles that assessed the double checking process during the administration of medicines. Sixteen articles were identified. Only one of them was a randomised controlled clinical trial in a clinical setting. Only one study was conducted in a children's hospital. The review found that there is insufficient evidence to either support or refute the practice of double checking and more clinical trials are needed to evaluate the double checking process in children's hospitals. Based on the findings that were highlighted from the systematic review, a prospective observational study of paediatric nurses using the double checking process for medication administration was undertaken. The study aimed to evaluate how closely double checking policies are followed by nurses in different paediatric areas, and also to identify any. medication administration errors during the study period. 2,000 drug dose administration events were observed. There was variation between paediatric nurses adherence to double checking steps and different medication administration errors were identified. Based on the observational study, a semi-structured questionnaire study was developed. It was designed to explore the paediatric nurses' knowledge and opinions about the double checking process. The study showed that many nurses have insufficient knowledge on the double checking process and the hospital policy for medication administration. A simulation study was conducted to examine whether single or double checking is more effective in detecting and reducing medication errors in children. Each participant in this study was required to prepare and administer medicines in scenarios for two "dummy patients" either with another nurse (double checking) or alone (single checking). Different confounders were built into each scenario (prescribing and administration) for nurses to identify and address during the administration process. Errors in drug preparation, administration and failure to address confounders were observed and documented. The main findings from this study were that the double checking process is more likely to identify medication administration errors and contraindicated drugs than single checking. The time taken for drug administration was similar for both processes. Another systematic review was conducted to identify the published medication errors studies that have been undertaken in the Middle East. The review identified 45 studies from 10 Middle Eastern countries. Nine of the studies focused on medication errors in paediatric patients. Educational programmes on drug therapy for doctors and nurses are urgently needed in the Middle East. These studies have contributed to the field of medication safety by providing more information about double and single checking medication administration processes in paediatric hospitals. More educational and training programmes for nurses about the importance of double checking and improving their adherence rate to the double checking steps during medication administration are required to improve its effectiveness.